Intravitreal anti-vascular endothelial growth factor treatment in patients with radiation retinopathy following plaque radiotherapy for uveal melanoma - E.P. Sudakova; V.A. Yarovaya; E.O. Malakshinova (Офтальмохирургия)
Relevance. Radiation retinopathy and maculopathy are the most common causes of visual impairment in patients with uveal melanoma treated with plaque radiotherapy. There are no standards of medical care for such patients, and various therapeutic methods of treatment are limited by rather poor results. The use of vascular endothelial growth factor inhibitors is proposed worldwide to improve visual acuity or stabilize one’s with the development of post-radiation retinopathy, even though today the use of such methods is «off label». Purpose. To analyze the development of radiation maculopathy in patients with uveal melanoma treated with plaque radiotherapy and its intravitreal anti–vascular endothelial growth factor treatment. Material and methods. To perform the review, a search was carried out for literature sources on the Pubmed and Scopus reference databases for the period up to 2022 inclusive using the following keywords: «uveal melanoma», «radiation maculopathy», «anti-vascular endothelial growth factor», «plaque therapy complications». A total of 39 articles related to the review topic were selected. Results. It can be concluded that intravitreal anti-vascular endothelial growth factor treatment of uveal melanoma shows its effectiveness in reducing the height of macular edema and in improving visual acuity. Conclusion. This method of therapy certainly necessitates repeated treatment, since with single injections it is not possible to achieve a positive result. However, it is impossible o predict how much vision will improve and how many injections of drugs each individual patient will need today.